3D virtual worlds as collaborative communities enriching human endeavours: Innovative applications in e-learning - Dreher, Carl; Reiners, Torsten; Dreher, Naomi; Dreher, Heinz (Institute of Electrical and Electronics Engineers (IEEE) Industrial Electronics Society, 2009)
3D virtual worlds are potent digital ecosystems because the 3D interface simulates real-world environments and the community of users creates a dynamic, real-to-life economy and in-world culture. Some virtual worlds such as Second Life empower users to generate in-world content through object building tools and programming languages; indeed the content in Second Life is entirely user-generated. This promotes a rich culture of innovation surrounding this emerging technology that continually develops the capabilities of the 3D digital ecosystem. The collaborative culture spans both the 3D in-world environment and 2D ecosystems: for example, Web 2.0 applications such as wikis and blogs facilitate support, discussion, and documentation for user-generated innovations. Innovation in 3D digital ecosystems such as Second Life are applied to all domains of human endeavour that exist in the real-world, including recreation, socialisation, commerce, and education. This paper shares the authors professional experience using Second Life in tertiary information systems/science education. Case studies describe the specific applications. They are followed by discussion of the benefits of 3D digital ecosystems for education and suggestions for future research, development, and practice.